Experimental study on disinfection effect of different dose of rapid hand disinfectant - Xiuhua Li; Chun-Juan Xu; Shu-Juan Zhao (Elsevier, 2014)
Purpose: To investigate the appropriate antiseptic handrubbing method. Methods: Seventy-four clinical nurses were randomly divided into two groups based on the number of disinfectant presses used, with group 1 using one-press and group 2 using two-presses. Sterilizing effects as a function of presses were compared and analyzed between the two groups. Results: Prior to hand disinfection, the hand sampling region resulted in 72 colony forming units for the 74 nurses. Following disinfection, only 2 colony forming units (p < 0.001) were found. The analysis of drying time effects on the disinfection rate between the two groups showed a significant difference (p = 0.049). Conclusion: In an effort to reduce the incidence of nosocomial infection, the medical personnel should sufficiently dry hands following handrubbing with disinfectant in a strict accordance with the six part washing technique for antiseptic handrubbing.